2017
DOI: 10.21276/aimdr.2017.3.3.pt3
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Breast Lesions Diagnosed on Fine Needle Aspiration Cytology in Rural Population of Khanpur Kalan, Sonepat (Haryana)

Abstract: Background: Breast or mammary gland is under the influence of hormones resulting in physiological changes throughout reproductive life and thereafter various structures give rise to different lesions. FNAC can be used as an OPD procedure in diagnosis of breast lesions without the need to hospitalize the patient. AIM: To study the spectrum of breast lesions in rural population of Haryana. Methods: Breast Lump is the commonest presenting symptom in various types of Breast lesions ranging from inflammation to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(9 reference statements)
2
3
0
Order By: Relevance
“…5 Malignant smears are mostly invasive ductal carcinoma in females. Only 11% smears were categorized as malignant in present study which is in concordance with a study published by Kamra et al 22 However, it is in contrast to the findings reported by Arul et al 6 and Madubogwu et al 23 who found much higher frequency (35%) and (34.6%) in their studies respectively. Similar higher frequencies (36.95% and 22%) are reported in local studies.…”
Section: Discussionsupporting
confidence: 90%
“…5 Malignant smears are mostly invasive ductal carcinoma in females. Only 11% smears were categorized as malignant in present study which is in concordance with a study published by Kamra et al 22 However, it is in contrast to the findings reported by Arul et al 6 and Madubogwu et al 23 who found much higher frequency (35%) and (34.6%) in their studies respectively. Similar higher frequencies (36.95% and 22%) are reported in local studies.…”
Section: Discussionsupporting
confidence: 90%
“…4). were malignant which is comparable to studies conducted by Rasheed et al [1] (80.7% benign,19.30% malignant), Hatim et al [2] (80% benign), Kamra T et al [3] (83.86% benign,11.19% malignant), Khanna R et al [4] (61.40% benign,39.60% malignant), Tawfeek T et al [5] (60.20% benign,21.20% malignant) and Parajuli S et al [6] (87% benign, 13% malignant).…”
Section: Resultssupporting
confidence: 88%
“…In the absence of stroma, numerous single bipolar nuclei are highly suggestive of the diagnosis. In the present study, fibroadenoma was the most common benign lesion which was seen most commonly in the younger [13,14,15] Out of the remaining 6 cases, 3 were mucinous carcinoma which showed moderately cohesive epithelial cells with abundant cytoplasm and moderate nuclear enlargement and atypia with abundant background mucin, one was a plasmacytoid variant of carcinoma a differential of plasmacytoma was also rendered in this 60 year old female and 2 were categorized as metaplastic carcinoma of which smears showed squamous differentiation along with high-grade carcinoma.…”
Section: Resultsmentioning
confidence: 50%